Chinese Doctoral Students Involved in Interdisciplinary Learning Score Higher on Scientific Creativity: The Roles of Teamwork Skills and Collaborative Behaviors - Shuzhen Chen; Lichao Ma; Yinqi Ma (Behavioral Sciences, 2024)
Despite the growing recognition of the value of interdisciplinary learning in doctoral education, there is still a gap in the literature supporting the relationship between it and doctoral students’ scientific creativity in China. Based on a questionnaire survey of 457 doctoral students from the humanities and social sciences on the Chinese Mainland, this study adopted structural equation modeling to examine the relationships among interdisciplinary learning, teamwork skills, collaborative behaviors, and scientific creativity. The results indicated that there was a weak positive correlation between interdisciplinary learning and the scientific creativity of doctoral students. Teamwork skills mediated the relationship between interdisciplinary learning and creativity, while the mediating effect of collaborative behaviors did not hold. Moreover, the relationship between interdisciplinary learning and creativity can also be mediated by the sequential mediation of teamwork skills and collaborative behaviors.